Knowledge, Attitude and Associated Factors Towards Vasectomy Among Married Men in Arba Minch Town, Southern Ethiopia, 2021; A Cross-Sectional Study - Dejene Wolde Y; Ali M; Gebremeskel F; Ukke GG; Gebreselassie R; Demelash M; Kebede A; Hailu M (Dove Medical Press, 2023)
Yesuneh Dejene Wolde,1 Momina Ali,2 Feleke Gebremeskel,3 Gebresilasea Gendisha Ukke,4 Rediet Gebreselassie,1 Minychil Demelash,1 Abebaw Kebede,5 Michiale Hailu2 1Department of Midwifery, College of Medicine and Health Sciences, Wachemo University, Hossana, Ethiopia; 2Department of Midwifery, College of Medicine and Health Sciences, Dire Dawa University, Dire Dawa, Ethiopia; 3School of Public Health, College of Medicine and Health Sciences, Arba Minch University, Arba Minch, Ethiopia; 4Department of Midwifery, College of Medicine and Health Sciences, Arba Minch University, Arba Minch, Ethiopia; 5Department of midwifery, College of Medicine and Health Sciences, Bule Hora University, Dire Dawa, EthiopiaCorrespondence: Yesuneh Dejene Wolde, Email yesudeye27@gmail.comBackground: Vasectomy is a safe and effective permanent contraceptive method. In Ethiopia, this method underutilized since the focus has been on contraceptive methods available for women rather than men. Few studies have examined this method in Ethiopia so far, so it is important to note that there is a lack of data about the method in the study area regarding married men's knowledge and attitudes toward vasectomy.Methods: A community-based cross-sectional study conducted from May 2 to June 2, 2021, at Arba Minch town. A simple random sampling technique used to select 624 study participants. Data collected via the face-to-face interview technique using a semi-structured and pretested questionnaire. Data entered in EpiData 3.1, cleaned, and analyzed using SPSS for Windows version 25.0. Descriptive statistics and bivariable and multivariable logistic regression analyses were performed. An adjusted odds ratio (AOR) with 95% CI and a p-value < 0.05 estimated to identify statistically significant variables associated with knowledge and attitude towards vasectomy.Results: From the total of 624 study subjects, 600 had completed the questionnaire, giving a response rate of 96.2%. From those who heard about vasectomy (36.8%), only 60.6% of men had good knowledge, and 48.4% had a positive attitude towards vasectomy. Men's knowledge of vasectomy was significantly associated with college or university attendance (AOR = 4.05, 95% CI: 1.720- 9.521), age 31- 40 years (AOR = 2.308, 95% CI: 1.081- 4.929), and age ≥ 41 years (AOR = 2.671, 95% CI: 1.159- 6.156). Age ≥ 41 years (AOR=4.735 95% CI 2.015- 11.129), age of last child (AOR=3.868 CI 1.554- 9.632) and discussing family planning with wife (AOR=2.821 95% CI 1.559- 5.105) were significantly associated with attitude of men towards vasectomy.Conclusion: In this study area, six out of ten and half of the married men had good knowledge and a positive attitude towards vasectomy, respectively.Keywords: vasectomy, knowledge, Arba Minch